Epigallocathecahin-3-gallate antimycotic and azole resistant modulator potential against triazole-resistant aspergillus fumigatus - Ponte, Tomás Saraiva (2021)
Project "Resistant mycobiota and mycotoxigenic profile of tea and medicinal plants” (IPL/2020/TEAResMyc_ESTeSL)